Managing Connection Based Access Control Systems on the other hand Mobile Devices - Venkatesan, S; Renuka Devi, K (International Journal of Computer Sciences and Engineering, 2025)
An android is a name given to a versatile working structure made by Google. A working structure is programming that acts as an interface also, manages PC equipment also, programming resources. In any other working system, there is a issue of malevolent programming on the other hand noxious contents attempting to wreak havoc. A noxious programming is any programming that is utilized on the other hand on the other hand can disrupt PC operation also, gather access to private structures .Android applications will frequently have access to private also, grouped resources also, data in the client’s device. There is high degree of conceivable misuse of these resources. We can take an illustration of an application utilizing a feature camera to document the on-going exercises of an organization. Android customers do have a certain sum of control over the application limits also, limits after installing it based on client’s connection. In our paper, we propose another way where system managers can control what applications are granted access on the other hand revoked.